Evaluasi Manajemen dalam Lembaga Pendidikan Tinggi - Nurul Oktaviana Mekawati; Herianto Herianto; Messiono Messiono (Universitas Batanghari Jambi, 2023)
Higher education institutions or higher education institutions are education units that organize education and can take the form of academies, polytechnics, high schools, institutes, or universities. Universities are obliged to organize education, research, and community service. The existence of this educational institution must of course be accompanied by optimal management of education for the creation of a generation of nations. To determine the success of the education management program implemented, an evaluation is needed. This study uses the literature study method which aims to find out the discussion on management evaluation in higher education institutions. The data analysis technique used in this research is content analysis. The results of the research show that (1) higher education management should be organized using flexible, dynamic, and quality-oriented management principles to enable each tertiary institution to grow and develop according to its potential. (2) evaluation of management in higher education institutions must be carried out to determine policies that support the creation of the best education. (3) Realizing a quality tertiary institution requires